Ovarian hyperstimulation syndrome (OHSS) in spontaneous pregnancy - khan, M.; Maslami, F.; Elhakim, E. (Scientific Journal of Medical Science, 2013)
It has been known that most cases of ovarianhyperstimulation syndrome (OHSS) are almost exclusively associated withcontrolled ovarian stimulation with gonadotrophins or occasionally, clomiphenecitrate. However, OHSS is also infrequently associated with a ontaneousovulatory cycle, usually in the case of multiple gestations, hypothyroidism, orsevere forms of polycystic ovarian syndrome. Severe OHSS associated with aspontaneously conceived prhyperstimulation syndrome (sOHSS) in a woman whoconceived spontaneously with no underlying disease. All associated risk factorswere excluded, such as multiple gestations, hypothyroidism, or polycysticovarian syndrome. Purpose of this case report is to discuss about the conditionwhich can be associated morbidity and even mortality, if remain undiagnosed andif not managed properly. Furthermore, it is interesting to note thatexploratory laparotomy was performed in six cases, because an ovarian cancerwas suspected. Therefore, clinicians must bear the differential diagnosis ofOHSS in mind if a patient presents with gross ascites and other symptoms ofovarian cancer, which also may be signs of OHSS. This case report emphasis that by taking allpossible differential diagnoses intoaccount, unnecessary laparotomy may be avoided pregnancy is are with only fewprevious reports.